Distinguishing neural ensembles in the infralimbic cortex that regulate stress vulnerability and coping behavior - Jenna L. Laymon; Conner J. Whitten; Anna F. Radford; Alonnah R. Brewer; Yash S. Deo; Mackenzie K. Hooker; Akhil A. Geddati; Matthew A. Cooper (Neurobiology of Stress)
Neural ensembles in the medial prefrontal cortex regulate several types of responses to stress. We used a Syrian hamster model to investigate the role of infralimbic (IL) neurons in coping with social defeat stress and vulnerability to subsequent anxiety-like behavior. We created social dominance relationships in male and female hamsters, used a robust activity marker (RAM) approach to label IL neural ensembles activated during social defeat stress, and employed light-dark (LD), social avoidance (SA), and conditioned defeat (CD) tests to assess anxiety-like behavior. We found that dominant animals were less anxious in LD tests compared to subordinate animals after achieving their higher status. Also, status-dependent differences in anxiety-like behavior were maintained following social defeat in males, but not females. Subordinate males showed greater RAM-mKate2 expression in IL parvalbumin (PV) cells during social defeat exposure compared to dominant males, and submissive behavior during CD testing was correlated with RAM/PV co-expression. In contrast, greater RAM-mKate2 expression in IL neurons was correlated with a longer latency to submit during social defeat in dominant females, although the correlation of RAM/PV co-expression and defeat-induced anxiety in females was mixed. Overall, these findings suggest that activation of IL PV cells during social defeat predicts the development stress vulnerability in males, whereas activation of IL neurons is associated with a proactive response to social defeat exposure in females. Understanding how social dominance generates plasticity in IL PV cells should improve our understanding of the mechanisms by which behavioral treatments prior to stress might promote stress resilience.